Multi-century mean summer temperature variations in the Southern Rhaetian Alps reconstructed from Larix decidua blue intensity data - R. Cerrato; M. C. Salvatore; M. C. Salvatore; M. Brunetti; A. Somma; C. Baroni; C. Baroni (Climate of the Past)
Ongoing climate change is likely to cause a worldwide temperature increase of 1.5 °C by the mid-century. To contextualize these changes in a long-term context, historical climatological data extending beyond data obtained from instrumental records are needed. This is even more relevant in remote areas characterized by complex climatic influences and where climate sensitivity is pronounced, such as the European Alps. Considering their high temporal resolution, dendrochronological data have been recognized as a fundamental tool for reconstructing past climate variations. In this study, we present a comprehensive dendroclimatic analysis in which blue intensity (BI) data derived from European larch (Larix decidua Mill.) trees in the Southern Rhaetian Alps were employed. By establishing the relationships between BI patterns in tree rings and climate variables, we explored the possibility of using the obtained data for constructing a high-resolution, long-term climate record. The results in the high-frequency domain showed that BI data from European larches explained up to 38.4 % (26.7 %–48.5 %) of the June–August mean temperature variance in the study area; this result is 70 % greater than the mean temperature variance percentages explained by total ring width measurements for the same period in the area. Moreover, the correlation values between the BI data and June–August mean temperature are stable over time, ranging between 0.40 and 0.71 (mean value of 0.57), considering a moving window of 50 years, and at spatial scale, with significant values over the western and central Mediterranean areas returned for all the considered time windows. In fine, the regression performance using BI data is comparable to that using data from more expensive methods of analysis. The results from this investigation will extend the current knowledge on the applicability of using BI data to study the European larch, and the reconstruction described herein is the first attempt to determine whether this proxy can be used for dendroclimatic aims. Thus, BI data represent a suitable tool for extending our knowledge beyond that obtained from instrumental records and for facilitating a more robust evaluation of climate models and future climate scenarios in the Alpine region.